Development of mobile application of event assistant and booking sport facilities for UiTM Seremban 3 Campus using wofkflow management system / Ahmad Haiqal Abd Halim, Ahmad Yusuf Che Hassan and Mohd Norhafizi Hambari - Abd Halim, Ahmad Haiqal; Che Hassan, Ahmad Yusuf; Hambari, Mohd Norhafizi (2019)
The manual processes for applying an event at UiTM Seremban 3 take several steps and day to get an approval. Due to this issue, the new method can be invented with current modem technology. Research is conducted to solve the problem by creating an application that fuses the Workflow Management System (WfMS) in the event application at UiTM. Currently, the application of the event firstly needs to be approved by the club advisor follow by UiTM administration then UiTM facilities and UiTM financial department. This main layer of approval can take many places to visit and time to take just to get an event approval. The integration of WfMS is a suitable method because it defines every important process and level of approval that the application needs to go through. The finding and study for this research can help the administration of UiTM to manage and process the number of event applications more efficient and faster. Besides, it will reduce the steps to get approval for any event. In this research, its content of the step on how to apply the method of WfMS in a mobile application with the use of an android studio. The algorithm for the WfMS is written using Java script in this research. The focus of this research is involving booking sports facilities and to get approval from HEA and HEP depends on the event. Lastly, this application will reduce the time ofa pproval because .this application uses the real-time database. Therefore, the interaction between the student and HEA and HEP will be reduced and shorten the time taken for the event to get approved.